STATUS OF THE IRRIGATION SYSTEM LA VICTORIA YAHUARCOCHA SOCAPAMBA THROUGH THE MEASUREMENT OF STREAM FLOW GAUGING, IBARRA CANTON, IMBABURA - Paspuel Pala , Lenin; Franco , Wilfredo; Caicedo Rosero, Diego (Tierra Infinita, 2023)
The study locates in Ibarra canton, Ecuador; Its object was to diagnosticate of the current state of irrigation system La Victoria, Yahuarcocha, Socapamba, which analyzed flow availability and its losses. The methodology for the analysis of the irrigation system was the measurement of the amount of liquid and analysis in field to identify the problems of infiltration. The results were that the irrigation system loses flow due to infiltration and improper handling by users.
Keywords: Amount of liquid; Irrigation; watershed; Hydric resource; Flow